Numerical analysis on heat transfer characteristics of ionic liquids in a tubular heat exchanger. Issue 8 (2nd July 2020) - Meikandan, M.; Ganesh Kumar, P.; Sundarraj, M.; Yogaraj, D.
ABSTRACT: The efficiency of the solar thermal system depends on the performance of the solar collectors. There is a need to operate solar collector at higher possible temperature to attain maximum efficiency limits. However, the performance of the collector system is limited by the heat transfer characteristics of the working fluid called as the heat transfer fluid (HTF). Water is widely used as the HTF in the solar collector, but the major problem of using water as the HTF is its limited operating temperature. The objective of the work is to investigate the heat transfer characteristics of ionic liquids in tubular heat exchanger (HE) suitable for the solar thermal application. The HE was designed for a heat duty of 1 kW based on the thermal transport property of available ionic liquids and the computational fluid dynamics (CFD) analysis was performed. The results indicate that there is only minimal deviation between the assumed and CFD data.